Encoding information into spatial modes of light - Ndagano, Irenge Bienvenu (My University, 2016)
Spatial modes of light hold the possibility to power the next leap in classical and quantum communications. They provide the ability to pack more information into light, even into single photons themselves, while increasing the level of information security. In this quest, spatial modes carrying orbital angular momentum (OAM) have come under the spotlight due to their discrete in nite dimensional Hilbert space allowing, in theory, for an in nite amount of information to be carried by a photon. Here we study, theoretically and experimentally, spatial modes of two avours: scalar and vector modes. the dichotomy between the two avours is in their polarisation characteristics: scalar modes have spatially homogeneous polarisation elds, while vector modes do not. One facet of our work focusses on scalar mode carrying OAM; using digital holographic methods, we demonstrate the techniques used to tailor and analyse scalar optical elds. We discuss principles of generation and detection for scalar modes based on manipulations of the dynamic phase of light with spatial light modulators. We apply these techniques to characterise free-space and optical bre links, and demonstrate an increase in bandwidth with the additional modal channels. In the other facet of our work, we study vector vortex modes. A particular property exhibited by these modes is the non-separability of their degrees of freedom, a property traditionally associated with entangled quantum states. This raises the question: could quantum entangled systems be modelled with bright sources of vector vortex modes? We answer this question by applying vector vortex modes to the study of quantum transport of entangled states. We borrow techniques from quantum mechanics to evaluate the degree of non-separability of vector vortex modes, using the concurrence as our measure. By determining the evolution of the concurrence, and therefore the entanglement, of vector vortex modes in bres and free-space turbulent channels, we show that indeed, bright classical sources can be used to model the evolution of entangled quantum states in these channels.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, May 3, 2016.
Keywords: Light; Photons; Quantum communications